Antioxidant and free radical scavenging profile in milk of various indigenous cattle breeds of cattle - Singh, Navav; Sanjita Sharma; Vishnu Sharma; Manish Agarwal; Sita Ram Gupta; Prakash Chandra Sharma (Indian Journal of Dairy Science, 2022)
The present study was undertaken to investigate the total antioxidant and free radical scavenging activity in milk of zebu cattle viz. Kankrej, Sahiwal and Rathi during different lactation and parity in hot arid region of India. About 150 indigenous milking cattle (50 from each breed) viz. Kankrej, Sahiwal and Rathi were included in the study and 100 ml of milk sample was collected from four quarter of udder of lactating cows as pool sample from different Livestock research stations of Rajasthan University of Veterinary and Animal science, Bikaner. Milk samples were analyzed by one way ANOVA and DMRT (SPPS 24) to assess total antioxidant capacity and percent scavenging activity in milk. The results showed significant variation of antioxidant capacity (p<0.05) and percent scavenging activity (p<0.01) among three cattle breeds. Whereas Kankrej milk had the lowest total antioxidant capacity and percent scavenging activity. The highly significant variation (p<0.01) of total antioxidant capacity in different stage of lactation. Late stage of lactation accounted for significantly (P<0.05) higher total antioxidant capacity as compared to early stage of lactation. Total antioxidant capacity and percent scavenging activity were significantly (p<0.01) differed in different parity. Results of present study concluded that milk from the indigenous cattle breeds possess varied type and amount of antioxidants, which can be harnessed for promotion of different functional foods and further pharmaceutical preparations can be promoted for benefit of entrepreneurs and society.